My Health, My Language - multilingual video messages on health in Ireland - Catherine Clifford (James Cook University, 2023)
Introduction: In Ireland, 12% of the population was born outside of Ireland. Issues such as language, knowledge of entitlements and health systems may impact the health of some migrants and public health. Multilingual video messages have the potential to overcome some of these issues.Method: Video messages on twenty-one health topics in up to twenty-six languages have been created. They are presented by healthcare workers living and working in Ireland who originate from other countries in a friendly relaxed style. Videos are commissioned by the Health Service Executive, Ireland’s national health service. Scripts are written with medical, communication and migrant expertise. Videos are platformed on the HSE website, shared on social media, via QR code posters and by individual clinicians.Results: Video topics to date include how to access health care in Ireland, the role of a GP, screening services, vaccinations, antenatal care, postnatal health, contraception and breastfeeding. There have been over 200,000 views of videos. Evaluation is underway.Discussion: The importance of trusted information has been highlighted by the COVID-19 pandemic. Video messages presented by a professional who is culturally familiar have the potential to improve self-care, appropriate use of health services and uptake of prevention programmes. The format overcomes issues with literacy and a person can watch a video multiple times. Limitations include reaching those without internet access. Videos do not replace the need for interpreters but are a tool to improve understanding of systems, entitlements and health information, efficient for clinicians and empowering for individuals.